Association between urinary arsenic and the prevalence of endometriosis in women in the United States - Su, Luyang; Ren, Yanan; Xu, Ren; Zhao, Shixia; Liu, Weilan; Meng, Cuiqiao; Zhou, Xuan; Du, Zeqing (Frontiers in Public Health, 2025)
BackgroundEndometriosis affects up to 15% of women of reproductive age and can lead to various symptoms. More than 200 million people worldwide are at risk of higher than safe levels of arsenic exposure through drinking water. Studies investigating the relationship between arsenic and endometriosis are very limited and have yielded inconsistent results. This study aimed to explore the relationship between total urinary arsenic, arsenic species (Urinary arsenous acid, Urinary Arsenic acid, Urinary Arsenobetaine, Urinary Arsenocholine, Urinary Dimethylarsinic acid, Urinary Monomethylarsonic acid) and endometriosis.MethodsWe utilized a nationally representative dataset from the National Health and Nutrition Examination Survey (NHANES) from 2003 to 2006. A total of 650 participants were included. We examined the association between total urinary arsenic and different arsenic species with endometriosis using weighted multivariate logistic regression models.ResultsUrinary arsenous acid and urinary monomethylarsonic acid (MMA) were positively correlated with endometriosis (p < 0.05). After adjusting for potential confounding factors, the positive correlation of urinary MMA remained significant (OR: 1.317, 95%CI: 1.074–1.615). Subgroup analyses and interaction tests indicated that this association was not dependent.ConclusionOur research underscores a significant positive association observed between factors urinary MMA and endometriosis. Future research is needed to elucidate the specific mechanisms behind this association.